Proinflammatory cytokine profiling of tears from dry eye patients by means of antibody microarrays - Boehm, Nils; Riechardt, Aline I; Wiegand, Michaela; Pfeiffer, Norbert; Grus, Franz H (Investigative ophthalmology & visual science, 2011)
In the pathogenesis of keratoconjunctivitis sicca, immune processes are thought to play an important role. However, the exact details of the pathomechanisms are still unknown. In this study, the expression patterns of proinflammatory cytokines in the tears of patients with different subtypes of dry eye were analyzed. One hundred forty-three subjects subdivided into healthy controls (CTRL, n = 38), patients with aqueous-deficient dry eye (DRYaq, n = 35), patients with changes of the lipid layer (DRYlip, n = 36), and patients with a combination of both (DRYaplip, n = 34) were examined. Expression patterns of proteins (e.g., IL-1β, IL-6, ITNF-α, and IFN-γ) were examined using an advanced antibody microarray approach. Several highly significant differences in the cytokine levels of dry eye patients compared with healthy controls were detected. Patients with DRYaq or those with DRYaplip showed elevated levels for most of the tested proteins. For example, IL-1β was found to be elevated 2.4-fold in DRYaq patients and 2.75-fold in DRYaqlip patients (both P < 8.00E-6). The detected amounts of protein in DRYlip patients and in healthy controls showed only minimal differences (fold increase/decrease for all proteins >1.2; P > 5.00E-1). The similarity between the profiles of healthy controls and DRYlip patients justifies the assumption that the pathomechanism of this dry eye subtype is based on mechanisms other than inflammation, whereas it seems to be the case for DRYaq patients.